Escaping the split-level trap: postsuburban narratives in recent American fiction - Foster, Tim (2012)
My PhD engages with a number of recent works of fiction in order to understand how American literature has commented on the emergence of a postsuburban environment – that is to say a cosmopolitan landscape in which the previous city/suburb binary is no longer evident. Whilst the term 'postsuburban' is resistant to easy categorisation, I use it as a mode of enquiry both to reassess what fiction has to tell literary criticism about the foundational concept of suburbia, as well as to assess contemporary writing free from the assumptions of an inherited suburban imaginary. It is my thesis that these postsuburban environments are seen by the writers who set their fictions there as places that are far more than white middle-class dystopias, and that it is a fallacy to attribute to them, as certain literary critics do, the negative cultural clichés associated with postwar suburban fictions.